THE FIRST REPORT OF THE DIVERSITY OF ENSIFERA (INSECTA: ORTHOPTERA) FROM ROKAN HULU DISTRICT, RIAU PROVINCE - Sutrisno Syahlan; Rofiza Yolanda; Riki Riharji Lubis (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The objective of this study was to determine the diversity of the suborder Ensifera in Dusun 3, Rambah Hilir Tengah, Rambah Hilir Sub-District, Rokan Hulu District, Riau Province, Indonesia. The study was conducted from September 2015 to January 2016 at six sampling locations by sweep net and hand picking at day and night hours. We recorded 17 species of the Ensifera belonging to 12 genera, 2 families, and 10 subfamilies. The diversity comprised of Conochepalus maculatus, Conochepalus melaenus, Conochepalus sp., Elbenia sp., Elimaea sp., Euscyrtus concinnus, Hexacentrus unicolor, Loxoblemus parabolicus, Mecopoda elongate, Mecopoda sp., Nisitrus vittatus, Orthelimaea sp., Podoscirtinae species 1 (unidentified), Teleogryllus emma, Teleogryllus sp., Trellius sp. and Xabea sp. The C. maculatus and E. concinnus were the predominant species in this study.